The Effect Of Box Jump Training On Improving The Explosive Power Of The Leg Muscles Of Volleyball Players At SMK Negeri 3 Seluma - Neta Selfiani; Suwarni Suwarni; Ajis Sumantri (Universitas Dehasen Bengkulu, 2026)
The problem of this research is that there are still many volleyball players of SMK Negeri 3 Seluma who complain of difficulty in doing smash and block because they do not have a high vertical jump. This study aims to determine the effect of box jump training on increasing the explosive power of leg muscles of Volleyball Players of SMK Negeri 3 Seluma. This type of research is an experiment, this type of research is research with experimental treatment. The sample in this study was 12 volleyball players of SMK Negeri 3 Seluma. The data analysis technique is using the t test. The results of the analysis show the effect of box jump training on increasing the explosive power of leg muscles of volleyball players of SMK Negeri 3 Seluma. where t count> t table (4.927> 1.795). It is recommended for volleyball coaches to create a suitable and appropriate training program for players to be able to improve the explosive power of leg muscles of players to be better.